2022
DOI: 10.3390/ijms232415980
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles for Topical Application in the Treatment of Skin Dysfunctions—An Overview of Dermo-Cosmetic and Dermatological Products

Abstract: Nanomaterials (NM) arouse interest in various fields of science and industry due to their composition-tunable properties and the ease of modification. They appear currently as components of many consumer products such as sunscreen, dressings, sports clothes, surface-cleaning agents, computer devices, paints, as well as pharmaceutical and cosmetics formulations. The use of NPs in products for topical applications improves the permeation/penetration of the bioactive compounds into deeper layers of the skin, prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 451 publications
0
28
0
3
Order By: Relevance
“…Given that the healthy skin's pH varies from 4.5 to 5.5 clay samples in this study recorded acidic pH and they may be deemed appropriate for cleansing applications, as there is little chance of a chemical reaction happening when clay samples are applied to the skin 36 . Therefore, the skin remains unharmed when utilizing them as cleansers since highly alkaline cosmetic cleansers possess a significant propensity to prompt skin irritation 37 . They can also damage the stratum corneum's lipid bilayer, which can result in dryness and itching after skin wash 38 .…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Given that the healthy skin's pH varies from 4.5 to 5.5 clay samples in this study recorded acidic pH and they may be deemed appropriate for cleansing applications, as there is little chance of a chemical reaction happening when clay samples are applied to the skin 36 . Therefore, the skin remains unharmed when utilizing them as cleansers since highly alkaline cosmetic cleansers possess a significant propensity to prompt skin irritation 37 . They can also damage the stratum corneum's lipid bilayer, which can result in dryness and itching after skin wash 38 .…”
Section: Resultsmentioning
confidence: 93%
“…36 Therefore, the skin remains unharmed when utilizing them as cleansers since highly alkaline cosmetic cleansers possess a significant propensity to prompt skin irritation. 37 They can also damage the stratum corneum's lipid bilayer, which can result in dryness and itching after skin wash. 38 Matike et al reported that the pH values ranged from 4.5 to 9.5 after examining 40 clay samples that were used in South Africa for cosmetic purposes. 39 In their study, they further revealed that samples used for sunscreens had mean pH values around 6.31 and those used for body beautification had mean pH ranging from 7.4 to 9.5.…”
Section: Of Analyzed Clay Soilsmentioning
confidence: 99%
“…The nanoparticulate systems show great potential in the topical delivery of actives for the treatment of skin diseases. The extensive research from current years supports the increasing interest in various lipid and polymeric nanovectors containing not only corticosteroids, but also many more actives for (trans)dermal delivery [ 83 , 84 , 85 ]. However, there are rather few studies comparing the efficiency of different types of nanosystems for specific drugs.…”
Section: Resultsmentioning
confidence: 99%
“…11 The use of nanoparticles in topical formulations enhances the permeation and penetration of bioactive compounds into the deeper layers of the skin. 12 Invasomes are novel lipid-based nanovesicles that can provide better skin penetration compare with conventional liposomes. 13,14 These vesicles are mainly composed of phospholipids, ethanol and terpenes that give soft and flexible properties.…”
Section: Introductionmentioning
confidence: 99%
“…Nanotechnology is an attractive field of research that fabricates structures on the nanoscale by utilizing novel design, fabrication, characterization and application techniques 11 . The use of nanoparticles in topical formulations enhances the permeation and penetration of bioactive compounds into the deeper layers of the skin 12 . Invasomes are novel lipid‐based nanovesicles that can provide better skin penetration compare with conventional liposomes 13,14 .…”
Section: Introductionmentioning
confidence: 99%